2020
DOI: 10.5001/omj.2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio as an Alternative Marker of Neonatal Sepsis in Developing Countries

Abstract: Objectives: We sought to analyze the neutrophil-to-lymphocyte ratio (NLR) as an alternative marker of neonatal sepsis. Methods: In this cross-sectional study, we undertook consecutive sampling in all inborn neonates admitted to the Neonatal Intensive Care Unit with clinical manifestations of neonatal sepsis. Neonates with congenital anomalies and referred neonates were excluded. Complete blood count, C-reactive protein (CRP), and blood culture were carried out as the septic workup examinations based on the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
(23 reference statements)
3
16
0
1
Order By: Relevance
“…This finding is incongruous to Sucilathangam et al, where they found that 85% of culture-positive neonates had a normal WBC count [11]. Similarly, Sumitro et al reported in their study that around 90% of septic neonates had a WBC count within the normal range [12]. In two multicentric studies, the WBC count and ANC count were studied, and they did not perform well as a standalone diagnostic tool for early-onset neonatal sepsis in late-preterm and term neonates.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This finding is incongruous to Sucilathangam et al, where they found that 85% of culture-positive neonates had a normal WBC count [11]. Similarly, Sumitro et al reported in their study that around 90% of septic neonates had a WBC count within the normal range [12]. In two multicentric studies, the WBC count and ANC count were studied, and they did not perform well as a standalone diagnostic tool for early-onset neonatal sepsis in late-preterm and term neonates.…”
Section: Discussionmentioning
confidence: 70%
“…Babies who presented within the first 72 hours of birth with signs of sepsis were diagnosed as early-onset sepsis while those who presented later were classified as late-onset sepsis. In a similar kind of study population from Indonesia, the median NLR value of septic neonates 3.63 was higher compared to an NLR of 2.12 in the suspected sepsis group, with an AUC of 0.63 [12].…”
Section: Discussionmentioning
confidence: 71%
“…Table [3] shows that Klebsiella was the most common organism in blood culture [20%] followed by E. coli and group B streptococci [13.3%].…”
Section: Resultsmentioning
confidence: 99%
“…As for the time of symptoms onset, they are categorized as Early-Onset Sepsis [EOS] and Late-Onset Sepsis [LOS]. In case the neonate is presented with clinical signs and inflammation with increase in the biomarker, but the blood culture is negative, then sepsis is defined as clinical Sepsis [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal sepsis is a major issue to deal with worldwide and contributes to significant morbidity and mortality, especially in developing countries with an incidence of 10-50 per 1000 live births [ 7 ]. India has the highest incidence of sepsis (17,000/1,00,000 live births), with the case fatality rate of neonatal sepsis ranging between 25% to 65% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%